A mathematical description of nerve fiber bundle trajectories and their variability in the human retina - Jansonius, Nomdo; Nevalainen, J.; Selig, B.; Zangwill, L. M.; Sample, P. A.; Budde, W. M.; Jonas, Jost B.; Lagrèze, W. A.; Airaksinen, P. J.; Vonthein, R.; Levin, L. A.; Paetzold, J.; et al. (Vision research, 2009)
We developed a mathematical model wherein retinal nerve fiber trajectories can be described and the corresponding inter-subject variability analyzed. The model was based on traced nerve fiber bundle trajectories extracted from 55 fundus photographs of 55 human subjects. The model resembled the typical retinal nerve fiber layer course within 20° eccentricity. Depending on the location of the visual field test point, the standard deviation of the calculated corresponding angular location at the optic nerve head circumference ranged from less than 1° to 18°, with an average of 8.8°.
Gesehen am 18.07.2023